Microcrystalline quartz ceramic as well as preparation method and application thereof
Through spray drying and mechanical static pressure treatment of nano-amorphous silica, microcrystalline quartz ceramics are prepared with good high temperature resistance, which solves the problems of insufficient temperature resistance and bending strength of existing quartz ceramics and achieves high high temperature resistance and the effect of high bending strength expands its application range.
Patent Information
- Application Number
- CN202411317863.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-20
AI Technical Summary
The existing quartz ceramics have shortcomings in temperature resistance and bending strength, and it is difficult to improve their high temperature resistance and strength at the same time.
Nano-amorphous silica and nucleating agent are used as raw materials to prepare microcrystalline quartz ceramics by spray drying, mechanical static pressure and microcrystallation treatment to form microcrystalline quartz ceramics with good high temperature resistance and high bending strength.
It significantly improves the high temperature resistance and bending strength of quartz ceramics, and expands its application range. It is suitable for single crystal silicon rod drawing, diffusion tube, quartz boat, single crystal silicon feeding tube and high temperature windows.
Smart Images

Figure CN119241077A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quartz ceramics, and in particular to microcrystalline quartz ceramics and a preparation method and application thereof. Background Art
[0002] Quartz ceramics are a heat-resistant material with excellent shock resistance, extremely low expansion coefficient and thermal conductivity. They are currently widely used in aerospace, glass, photovoltaic and other fields. At present, quartz ceramics are generally processed using fused quartz powder or quartz glass powder as raw materials, which can replace quartz glass. However, the temperature resistance and strength of quartz ceramics are still insufficient, so quartz ceramics with good temperature resistance and high strength have always been a hot topic of research at home and abroad.
[0003] The existing technology mainly adopts the following two routes to improve the temperature resistance and strength of quartz ceramics:
[0004] Route 1: Adding high-temperature resistant materials such as silicon nitride into quartz ceramics. Although this doping method can improve the heat resistance of quartz ceramics, the bending strength can only be increased from 20-30MPa to 40-50MPa.
[0005] Route 2: By doping with substances such as boron oxide, lead oxide, and vanadium pentoxide, the bending strength of quartz ceramics is increased to about 50 MPa, but the temperature resistance cannot be improved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing microcrystalline quartz ceramics. The obtained microcrystalline quartz ceramics have good high temperature resistance and high bending strength. They can be made into crucibles for drawing single crystal silicon rods, and can also be used to make diffusion tubes, quartz boats, single crystal silicon feeding tubes, high temperature windows, etc.
[0007] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:
[0008] One of the purposes of the present invention is to provide a method for preparing microcrystalline quartz ceramics, comprising the following steps:
[0009] (1) adding nano-amorphous silica and a nucleating agent into water to prepare a slurry;
[0010] (2) spray drying the slurry to obtain nano-silicon dioxide agglomerates;
[0011] (3) mechanically and statically pressing the nano-silicon dioxide aggregates to obtain silicon dioxide green embryos;
[0012] (4) The silicon dioxide embryo is microcrystallized to obtain microcrystalline quartz ceramics.
[0013] The second object of the present invention is to provide a microcrystalline quartz ceramic prepared by the above-mentioned preparation method.
[0014] The third object of the present invention is to provide the application of the aforementioned microcrystalline quartz ceramic in the crucible, diffusion tube, quartz boat, single crystal silicon feeding tube, and high temperature window processing for single crystal silicon rod pulling.
[0015] The beneficial effects of the present invention are as follows: the present invention uses nano-amorphous silicon dioxide and a nucleating agent as raw materials, and prepares microcrystalline quartz ceramics through spray drying, mechanical static pressing and microcrystallization treatment. The microcrystalline quartz ceramics have good high temperature resistance, high bending strength and a transparent appearance, which can greatly expand the application range of quartz ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 XRD pattern of the microcrystalline quartz ceramic prepared in Example 1;
[0017] Figure 2 This is a SEM image of the microcrystalline quartz ceramic prepared in Example 1;
[0018] Figure 3 This is the XRD pattern of the non-microcrystalline quartz ceramic prepared in Comparative Example 5. DETAILED DESCRIPTION
[0019] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments and diagrams.
[0020] The present invention provides a method for preparing microcrystalline quartz ceramics, comprising the following steps:
[0021] (1) adding nano-scale amorphous silica and a nucleating agent into water to prepare a slurry;
[0022] (2) spray drying the slurry to obtain nano-silicon dioxide agglomerates;
[0023] (3) mechanically and statically pressing the nano-silicon dioxide aggregates to obtain silicon dioxide green embryos;
[0024] (4) The silicon dioxide embryo is microcrystallized to obtain microcrystalline quartz ceramics.
[0025] Furthermore, the average particle size of the nano-scale amorphous silicon dioxide is 5 to 40 nm. Amorphous silicon dioxide is a non-crystalline silicon dioxide. The present invention uses nano-scale amorphous silicon dioxide as a raw material to prepare microcrystalline quartz ceramics.
[0026] Furthermore, the nucleating agent includes but is not limited to at least one of oxides, hydroxides, chlorides, sulfates, nitrates, carbonates, phosphates and acetates of Ba, Cr, La series elements and Ac series elements. In the present invention, the nucleating agent can be attached to the surface of the nano-silicon dioxide by adsorption or precipitation.
[0027] Furthermore, the solid content of the slurry is 5-50%. If the solid content is lower than the range, the powder obtained by spray drying has more fine particles and poor fluidity; if the solid content is higher than the range, the viscosity of the slurry is high and the nozzle is easily blocked.
[0028] Furthermore, the air inlet temperature of the spray drying is 280-350° C., and the air outlet temperature is 80-120° C. The nano-scale amorphous silicon dioxide is transformed into nano-silicon dioxide agglomerates by spray drying.
[0029] Furthermore, the average particle size of the nano-silicon dioxide agglomerates is 200-500 nm. If the particle size is too large, the uniformity will be poor; if the particle size is too small, it will be difficult to prepare. Of course, the particle size of the nano-silicon dioxide agglomerates is also affected by the particle size of the raw material nano-scale amorphous silicon dioxide.
[0030] Furthermore, the pressure of the mechanical static pressure is 5 to 600 MPa. Since the nano-silicon dioxide powder is very fluffy, if pressure is applied directly to the powder, it will expand again and become loose when the pressure is removed. Therefore, it is necessary to add water to make a slurry first, and then make large particles by spray drying. The role of mechanical static pressure is to overcome the repulsive force between nano-silicon dioxide particles, so that the distance between nano-silicon dioxide particles is closer, so that the product obtained after sintering has less pores.
[0031] Furthermore, the temperature of the microcrystallization treatment is 1100-1650°C for 2-5 hours, and after the treatment, the temperature is lowered to ambient temperature at a rate of 3000-8000°C / min. Rapid cooling can prevent the growth of crystal nuclei.
[0032] The present invention provides a microcrystalline quartz ceramic prepared by the above-mentioned preparation method.
[0033] Furthermore, the content of nucleating agent in the microcrystalline quartz ceramic is 0.01-20 ppm. Adding a small amount of nucleating agent is beneficial to controlling the concentration of crystal nuclei, while too much nucleating agent will aggregate into large crystals, resulting in poor bending strength.
[0034] Furthermore, the crystal size of the microcrystalline quartz ceramic is less than 3 μm.
[0035] The present invention also provides the use of the aforementioned microcrystalline quartz ceramic in the processing of crucibles, diffusion tubes, quartz boats, single crystal silicon feeding tubes, and high-temperature windows for pulling single crystal silicon rods.
[0036] Example 1
[0037] Amorphous silicon dioxide with an average particle size of 5 nm is added to water, and barium hydroxide is added at a ratio of 0.01 ppm to prepare a slurry with a solid content of 20%; the slurry is spray-dried (the inlet air temperature is 280° C., and the outlet air temperature is 80° C.) to obtain nano-silica agglomerates with an average particle size of 200 nm; the nano-silica agglomerates are subjected to mechanical static pressing (pressure of 100 MPa, time of 0.5 h) to obtain a silicon dioxide green body; the silicon dioxide green body is calcined at 1100° C. for 5 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 3000° C. / min to obtain microcrystalline quartz ceramics.
[0038] Example 2
[0039] Amorphous silicon dioxide with an average particle size of 30 nm is added to water, and barium hydroxide is added at a ratio of 20 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 350° C., and the air outlet temperature is 120° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 300 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 250 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1650° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 8000° C. / min to obtain microcrystalline quartz ceramics.
[0040] Example 3
[0041] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, and barium hydroxide is added at a ratio of 5 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain microcrystalline quartz ceramics.
[0042] Comparative Example 1
[0043] The method of Example 3 is followed, except that amorphous silicon dioxide with an average particle size of 2 μm is used as the raw material.
[0044] Amorphous silicon dioxide with an average particle size of 2 μm is added to water, and barium hydroxide is added at a ratio of 5 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 300°C, and the outlet air temperature is 100°C) to obtain silicon dioxide agglomerates with an average particle size of 20 μm; the silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green body; the silicon dioxide green body is calcined at 1300°C for 2 h and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000°C / min to obtain non-microcrystalline quartz ceramics.
[0045] Example 4
[0046] The method of Example 3 was followed, except that barium hydroxide was replaced by barium chloride, and dilute sulfuric acid was added dropwise to adjust the pH value to 5.
[0047] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, barium chloride is added at a ratio of 5 ppm, and dilute sulfuric acid is added dropwise to adjust the pH value to 5 to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure is 150 MPa, time is 0.5 h) to obtain a silicon dioxide embryo; the silicon dioxide embryo is calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain microcrystalline quartz ceramics.
[0048] Example 5
[0049] The method of Example 4 was followed, except that the addition ratio of barium chloride was adjusted to 2 ppm.
[0050] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, barium chloride is added at a ratio of 2 ppm, and dilute sulfuric acid is added dropwise to adjust the pH value to 5 to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain microcrystalline quartz ceramics.
[0051] Example 6
[0052] The method of Example 3 was followed, except that the barium hydroxide was replaced by ammonium chromate and the addition ratio of ammonium chromate was 2 ppm.
[0053] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, and ammonium chromate is added at a ratio of 2 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain microcrystalline quartz ceramics.
[0054] Comparative Example 2
[0055] The method of Example 6 is followed, except that amorphous silicon dioxide with an average particle size of 2 μm is used as the raw material.
[0056] Amorphous silicon dioxide with an average particle size of 2 μm is added to water, and ammonium chromate is added at a ratio of 2 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the inlet air temperature is 300° C., and the outlet air temperature is 100° C.) to obtain silicon dioxide agglomerates with an average particle size of 20 μm; the silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green bodies; the silicon dioxide green bodies are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain non-microcrystallized quartz ceramics.
[0057] Example 7
[0058] The method of Example 3 was followed, except that barium hydroxide was replaced with gadolinium chloride and the addition ratio of gadolinium chloride was 1 ppm.
[0059] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, and gadolinium chloride is added at a ratio of 1 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano silicon dioxide agglomerates with an average particle size of 400 nm; the nano silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain microcrystalline quartz ceramics.
[0060] Comparative Example 3
[0061] The method of Example 7 is followed, except that amorphous silicon dioxide with an average particle size of 2 μm is used as the raw material.
[0062] Amorphous silicon dioxide with an average particle size of 2 μm is added to water, and gadolinium chloride is added at a ratio of 1 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain silicon dioxide agglomerates with an average particle size of 20 μm; the silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green bodies; the silicon dioxide green bodies are calcined at 1300° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain opaque non-microcrystalline quartz ceramics.
[0063] Example 8
[0064] The method of Example 3 is followed, except that barium hydroxide is replaced by cerium chloride and the addition ratio of cerium chloride is 1 ppm, and the cooling method is replaced by ice water rapid cooling.
[0065] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, and cerium chloride is added at a ratio of 1 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h, and then placed in ice water and cooled to ambient temperature at a cooling rate of 5000° C. / min to obtain microcrystalline quartz ceramics.
[0066] Comparative Example 4
[0067] The method of Example 3 is followed, except that the calcination temperature is adjusted from 1300°C to 1000°C.
[0068] Amorphous silicon dioxide with an average particle size of 50 nm is added to water, and barium hydroxide is added at a ratio of 5 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1000° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain non-microcrystalline quartz ceramics.
[0069] Comparative Example 5
[0070] The method of Example 3 was followed except that no nucleating agent was added.
[0071] Amorphous silicon dioxide with an average particle size of 50 nm is added to water to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C. and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 400 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 150 MPa for 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1300° C. for 2 h and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 6000° C. / min to obtain non-microcrystalline quartz ceramics.
[0072] Comparative Example 6
[0073] The method of Example 2 was followed, except that the addition ratio of barium hydroxide was adjusted to 500 ppm.
[0074] Amorphous silicon dioxide with an average particle size of 30 nm is added to water, and barium hydroxide is added at a ratio of 500 ppm to prepare a slurry with a solid content of 15%; the slurry is spray-dried (the air inlet temperature is 300° C., and the air outlet temperature is 100° C.) to obtain nano-silicon dioxide agglomerates with an average particle size of 300 nm; the nano-silicon dioxide agglomerates are subjected to mechanical static pressing (pressure of 250 MPa, time of 0.5 h) to obtain silicon dioxide green embryos; the silicon dioxide green embryos are calcined at 1650° C. for 2 h, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 8000° C. / min to obtain non-microcrystalline quartz ceramics.
[0075] Comparative Example 7
[0076] The method of Example 2 is followed, except that spray drying and mechanical static pressing are not performed, but slip casting is performed to obtain a silicon dioxide green body.
[0077] Amorphous silicon dioxide with an average particle size of 30 nm is added to water, and barium hydroxide is added at a ratio of 20 ppm to prepare a slurry with a solid content of 15%; the slurry is cast to obtain a silicon dioxide embryo; the silicon dioxide embryo is calcined at 1650° C. for 2 hours, and then placed in liquid nitrogen and cooled to ambient temperature at a cooling rate of 8000° C. / min to obtain a porous quartz ceramic.
[0078] Figure 1 The XRD pattern of the microcrystalline quartz ceramic prepared in Example 1. Figure 1 It can be seen that sharp characteristic peaks appear in the spectrum, indicating that a crystal phase has appeared and microcrystalline ceramics have been formed.
[0079] Figure 2 This is a SEM image of the microcrystalline quartz ceramic prepared in Example 1. Figure 2 It can be seen that a structure in which fine crystals are interwoven has appeared in the microstructure of the product prepared in Example 1.
[0080] Figure 3 The XRD pattern of the non-microcrystalline quartz ceramic prepared in Comparative Example 5 is shown in FIG. Figure 3 It can be seen that the spectrum is a steamed bun peak with a relatively diffuse peak shape, and no obvious crystal diffraction peak appears, indicating that the product prepared in Comparative Example 5 is amorphous.
[0081] The quartz ceramic samples prepared in the above embodiments and comparative examples were tested for bending strength, light transmittance, softening temperature, and thermal expansion coefficient. The test results are shown in Table 1.
[0082] Bending strength test standard GB / T 37781-2019;
[0083] Light transmittance test standard GB / T 5137.2-2020;
[0084] Softening temperature test standard GB / T 28195-2011;
[0085] Thermal expansion coefficient test standard GB / T 16920-2015.
[0086] Table 1
[0087] Flexural strength(MPa) Light transmittance (%) Softening temperature(℃) Coefficient of thermal expansion Example 1 71.4 89.1 1781 <![CDATA[2.1×10 -7 / ℃]]> Example 2 72.1 89.3 1790 <![CDATA[2.1×10 -7 / ℃]]> Example 3 71.6 89.0 1786 <![CDATA[2.1×10 -7 / ℃]]> Comparative Example 1 26.5 3.6 1729 <![CDATA[5.4×10 -7 / ℃]]> Example 4 78.6 89.5 1785 <![CDATA[2.2×10 -7 / ℃ <!-- 5 -->]]> Example 5 77.2 89.3 1783 <![CDATA[2.2×10 -7 / ℃]]> Example 6 71.8 89.2 1780 <![CDATA[2.3×10 -7 / ℃]]> Comparative Example 2 27.3 3.3 1726 <![CDATA[5.4×10 -7 / ℃]]> Example 7 73.8 89.1 1788 <![CDATA[2.2×10 -7 / ℃]]> Comparative Example 3 28.3 4.1 1724 <![CDATA[5.4×10 -7 / ℃]]> Example 8 73.2 89.5 1782 <![CDATA[2.2×10 -7 / ℃]]> Comparative Example 4 27.2 4.0 1721 <![CDATA[5.4×10 -7 / ℃]]> Comparative Example 5 27.6 90.1 1728 <![CDATA[5.4×10 -7 / ℃]]> Comparative Example 6 26.8 58.7 1780 <![CDATA[5.4×10 -7 / ℃]]> Comparative Example 7 19.2 2.3 1710 <![CDATA[5.4×10 -7 / ℃]]>
[0088] From Table 1 we can see that:
[0089] Since Comparative Examples 1 to 3 use micron-sized amorphous silicon dioxide as raw material, the resulting quartz ceramics have poor light transmittance and high temperature resistance and low bending strength.
[0090] In Examples 4 and 5, the nucleating agent is attached to the surface of nano-silicon dioxide by precipitation method, so as to improve the bending strength of the prepared quartz ceramic.
[0091] In Comparative Example 4, due to the low calcination temperature, the quartz ceramic produced has poor light transmittance and high temperature resistance and low bending strength.
[0092] In Comparative Example 5, no nucleating agent was added. Although the produced quartz ceramic had good light transmittance, it had poor high temperature resistance and low bending strength.
[0093] In Comparative Example 6, since the proportion of the nucleating agent added is too large, the light transmittance of the prepared quartz ceramic decreases and the bending strength is low.
[0094] In Comparative Example 7, the silicon dioxide green body was prepared by slip casting instead of spray drying and mechanical static pressing. The flexural strength, light transmittance and softening temperature of the prepared quartz ceramic were the lowest among all comparative examples. This indicates that the spray drying and mechanical static pressing used in the process of preparing quartz ceramics of the present invention can effectively improve the light transmittance, high temperature resistance and flexural strength of the quartz ceramics.
[0095] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing microcrystalline quartz ceramics, characterized in that: The following steps are involved: (1) adding nano-scale amorphous silica and a nucleating agent into water to prepare a slurry; (2) spray drying the slurry to obtain nano-silicon dioxide agglomerates; (3) mechanically and statically pressing the nano-silicon dioxide aggregates to obtain silicon dioxide green embryos; (4) The silicon dioxide embryo is microcrystallized to obtain microcrystalline quartz ceramics.
2. The preparation method according to claim 1, characterized in that: The average particle size of the nano-scale amorphous silicon dioxide is 5 to 40 nm.
3. The preparation method according to claim 1, characterized in that: The nucleating agent includes, but is not limited to, at least one of oxides, hydroxides, chlorides, sulfates, nitrates, carbonates, phosphates, and acetates of Ba, Cr, La series elements, and Ac series elements.
4. The preparation method according to claim 1, characterized in that: The solid content of the slurry is 5 to 50%; Preferably, the inlet air temperature of the spray drying is 280-350°C, and the outlet air temperature is 80-120°C.
5. The preparation method according to claim 1, characterized in that: The average particle size of the nano silicon dioxide agglomerates is 200-500 nm.
6. The preparation method according to claim 1, characterized in that: The mechanical static pressure is 5-600 MPa.
7. The preparation method according to claim 1, characterized in that: The temperature of the microcrystallization treatment is 1100-1650° C., and the time is 2-5 hours. After the treatment, the temperature is lowered to ambient temperature at a rate of 3000-8000° C. / min.
8. Microcrystalline quartz ceramics prepared by the preparation method according to any one of claims 1 to 7.
9. The microcrystalline quartz ceramic according to claim 8, characterized in that: The content of the nucleating agent in the microcrystalline quartz ceramic is 0.01 to 20 ppm; Preferably, the crystal size in the microcrystalline quartz ceramic is less than 3 μm.
10. Use of the microcrystalline quartz ceramics according to claim 8 or 9 in crucibles for single crystal silicon rod pulling, diffusion tubes, quartz boats, single crystal silicon feeding tubes, and high temperature window processing.
Citation Information
Patent Citations
Quartz ceramic material and application for same
CN103145339A
Preparation method of fused quartz ceramic material containing nanoscale ytterbium oxide
CN103183502A
Preparation method of high-purity crystalline silicon dioxide particles
CN113307275A
Preparation method of high-purity cristobalite
CN116873943A
Partially crystallized silica glass and its production
JP1994191888A
